2011
DOI: 10.1007/s00181-011-0478-8
|View full text |Cite
|
Sign up to set email alerts
|

Are there different linkages of foreign capital inflows and the current account between industrial countries and emerging markets?

Abstract: This article investigates the causal relationship between the current account and foreign capital inflows on two groups of countries, industrial countries (ICs) and emerging markets (EMs), during the time period of 1987-2006. Apart from including three sets of control variables (macroeconomic, financial, and institutional) in the regression to avoid omitted variable bias, we additionally examine whether there is a disparate interaction between gross capital inflows and the current account and between net forei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
(42 reference statements)
1
5
0
Order By: Relevance
“…Yan and Yang (2012) proved on the comparative study of the industrial countries and the emerging markets in the period of 1987À2006 that foreign capital inflow, as the key contributor, resulted in much more serious current account deficit in the emerging countries as compared with the industrialized economies and led to inevitable currency crises. Similarly, Wei (2001) recognized a destructive effect of the capital outflows from the emerging economies, especially if FDIs are combined with a substantial level of international bank loans.…”
Section: Fdis and The Emerging Markets Currency Crisesmentioning
confidence: 99%
“…Yan and Yang (2012) proved on the comparative study of the industrial countries and the emerging markets in the period of 1987À2006 that foreign capital inflow, as the key contributor, resulted in much more serious current account deficit in the emerging countries as compared with the industrialized economies and led to inevitable currency crises. Similarly, Wei (2001) recognized a destructive effect of the capital outflows from the emerging economies, especially if FDIs are combined with a substantial level of international bank loans.…”
Section: Fdis and The Emerging Markets Currency Crisesmentioning
confidence: 99%
“…Subramanian (2007) argues that capital flow may lead to appreciation of currency and worsening of the CA balance, thus affecting the competitiveness of an economy. Yan and Yang (2012), Yan and Yang (2012) have shown that the causality runs from the capital account to current account in case of developing countries and therefore it is the capital flow that causes the CA imbalance in these countries. Their study is more robust and has included various control variables in order to get rid of causal fallacy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The negative association between the two accounts is well justified theoretically (see the Equation [1] in section 3). Yan and Yang (2012) argued that a large capital inflow will result in capital account surplus, which can lead to both higher investment and extravagant consumption, and consequently produce CA deficit. Carranza and Wong (1999) argued that capital inflow worsens the CAB, both under flexible and fixed exchange rate, though through different routes.…”
Section: Unit Root Testmentioning
confidence: 99%
“…Majority of the studies in this context concentrate on the differing relationship between the two accounts in case of developing versus developed countries (Fry, Claessens, Burridge, & Blanchet, 1995;Yan, 2005;Yan & Yang, 2008, 2012. In general, the studies conclude that in the case of developed nations, the causality runs from the imbalances in the CA to the KA while in the case of the developing nations, this causality is reversed.…”
Section: Literature Reviewmentioning
confidence: 99%